2020
DOI: 10.1007/s12630-020-01733-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oxygenation during pediatric congenital cardiac surgery and its association with outcome: a retrospective observational study

Abstract: Purpose Non-invasive cerebral oxygen saturation (ScO 2 ) monitoring is an established tool in the intraoperative phase of pediatric congenital cardiac surgery (CCS). This study investigated the association between ScO 2 and postoperative outcome by investigating both baseline ScO 2 values and intraoperative desaturations from baseline. Methods All CCS procedures performed in the period 2010-2017 in our institution in which ScO 2 was monitored were included in this historical cohort study. Baseline ScO 2 was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…In our study we defined baseline values of oxygenation as the mean of those recorded during the 5-min interval prior to incision. Post-induction baseline values might be a better representation of physiologic conditions during surgery than awake baseline values and might therefore be a more realistic basis on which to determine treatment goals [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we defined baseline values of oxygenation as the mean of those recorded during the 5-min interval prior to incision. Post-induction baseline values might be a better representation of physiologic conditions during surgery than awake baseline values and might therefore be a more realistic basis on which to determine treatment goals [29].…”
Section: Discussionmentioning
confidence: 99%
“…In our study we defined baseline values of oxygenation as the mean of those recorded during the 5-min interval prior to incision. Post-induction baseline values might be a better representation of physiologic conditions during surgery than awake baseline values and might therefore be a more realistic basis on which to determine treatment goals [ 29 ]. It could be argued that the most substantial part of the damage to the kidneys will occur intraoperatively rather than during induction, and therefore deviations in oxygenation below a stable post-induction level height of oxygenation may be more relevant.…”
Section: Discussionmentioning
confidence: 99%
“…6 The intraoperative use of the cerebral rSO 2 in pediatric cardiac surgery has provided an early warning sign of hemodynamic or metabolic compromise, enabling early interventions to prevent or reduce the severity of potentially life-threatening complications. 7 Although some research groups have reported that the use of a CHD patient's baseline rSO 2 after the induction of anesthesia was helpful in predicting clinical outcomes, 8,9 the clinical utility of rSO 2 continues to be a matter of debate. 6 Actually, these studies 8,9 had several limitations due to the study design and a previous study 10 showed that rSO 2 and ScvO 2 showed a significant correlation but absolute values of ScvO 2 tended to overestimate the correspondent rSO 2 values.…”
Section: Introductionmentioning
confidence: 99%
“…7 Although some research groups have reported that the use of a CHD patient's baseline rSO 2 after the induction of anesthesia was helpful in predicting clinical outcomes, 8,9 the clinical utility of rSO 2 continues to be a matter of debate. 6 Actually, these studies 8,9 had several limitations due to the study design and a previous study 10 showed that rSO 2 and ScvO 2 showed a significant correlation but absolute values of ScvO 2 tended to overestimate the correspondent rSO 2 values. One of the reasons why the value of rSO 2 monitoring in CHD patients is not established may be that the anatomic and physiological factors affecting cerebral and somatic rSO 2 have not been sufficiently clarified.…”
Section: Introductionmentioning
confidence: 99%
“…NIRS monitoring is increasingly used in the perioperative and critical care setting (Biedrzycka and Lango, 2016;Scheeren et al, 2019;Vos et al, 2019a), e.g. for cerebral oxygen saturation monitoring (Lee et al, 2018;Weber and Scoones, 2019;Modestini et al, 2020) and for estimating tissue or organ perfusion by an indirect means (Scheeren, 2016). NIRS can be combined with a vascular occlusion test (VOT) (Vos et al, 2019a), which entails inflating a tourniquet rapidly above systolic blood pressure proximal to the NIRS StO 2 measurement site and subsequently deflating the tourniquet.…”
Section: Introductionmentioning
confidence: 99%